Techno-economic evaluation of revamping of coal-fired power plants in India. (9th May 2006) - Dutta, Animesh; Dutta, Shantanu; Basu, Prabir
A techno-economic feasibility study has been conducted to investigate the revamping of two 32 MWe Pulverised-Coal (PC) boilers with a number of firing options. The options investigated were: (1) conventional PC revamping, (2) replacement with a new PC boiler, (3) PC to Circulating Fluidised Bed (CFB) revamping, (4) replacement with a new CFB boiler, and (5) Bubbling Fluidised Bed (BFB) revamping. The study reveals that: (i) CFB revamping of the boilers is technically feasible and economically viable; (ii) Performance improvement of the plant is significant in terms of such indices as plant load factor, forced outage and auxiliary oil consumption; (iii) Significant improvement in emissions performance due to the reduction in emissions of NOx and fly ash is projected; (iv) CFB revamping option gives the highest return on investment compared to alternatives. Finally, to demonstrate the technical soundness and viability of the special design used in this revamping, a subscale CFB boiler has been designed and built at another power plant.